Diabetes in pregnancy and epigenetic mechanisms—how the first 9 months from conception might affect the child's epigenome and later risk of disease. Issue 10 (October 2019) - Hjort, Line; Novakovic, Boris; Grunnet, Louise G; Maple-Brown, Louise; Damm, Peter; Desoye, Gernot; Saffery, Richard
Summary: Diabetes in pregnancy is not only associated with increased risk of pregnancy complications and subsequent maternal metabolic disease, but also increases the risk of long-term metabolic disease in the offspring. At the interface between genetic and environmental factors, epigenetic variation established in utero represents a plausible link between the in utero environment and later disease susceptibility. The identification of an epigenetic fingerprint of diabetes in pregnancy linked to the metabolic health of the offspring might provide novel biomarkers for the identification of offspring most at risk, before the onset of metabolic dysfunction, for targeted monitoring and intervention. In this Personal View, we (1) highlight the scale of the problem of diabetes in pregnancy, (2) summarise evidence for the variation in offspring epigenetic profiles following exposure to diabetes in utero, and (3) outline potential future approaches to further understand the mechanisms by which exposure to maternal metabolic dysfunction in pregnancy is transmitted through generations.